2012
DOI: 10.1111/j.1365-2710.2012.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum dextromethorphan/dextrorphan metabolic ratio for CYP2D6 phenotyping in clinical practice

Abstract: SUMMARYWhat is known and Objective: Accurate prediction of actual CYP2D6 metabolic activity may prevent some adverse drug reactions and improve therapeutic response in patients receiving CYP2D6 substrates. Dextromethorphan-to-dextrorphan metabolic ratio (MR DEM WHAT IS KNOWN AND OBJECTIVECYP2D6 plays a pivotal role in the metabolism of many drugs. It is a highly polymorphic enzyme, and to date, more than 80 allelic variants alleles have been identified. 1 The variant alleles may encode proteins with normal (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 19 publications
4
31
0
2
Order By: Relevance
“…The age range in this study was similar to previous studies investigating CYP2D6 phenotype [24, 30, 31]. The established tolerability profile of dextromethorphan was further demonstrated by the fact that only one (~1%) participant in our study had mild and transient drowsiness [24, 28, 3133]. In CYP2D6 phenotyping, the requisite cutoff(s) may be obtained by subjecting data to a probit analysis, Receiver Operating Characteristics (ROC) or other similar statistical analysis [28, 33, 34].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The age range in this study was similar to previous studies investigating CYP2D6 phenotype [24, 30, 31]. The established tolerability profile of dextromethorphan was further demonstrated by the fact that only one (~1%) participant in our study had mild and transient drowsiness [24, 28, 3133]. In CYP2D6 phenotyping, the requisite cutoff(s) may be obtained by subjecting data to a probit analysis, Receiver Operating Characteristics (ROC) or other similar statistical analysis [28, 33, 34].…”
Section: Discussionsupporting
confidence: 85%
“…Dextromethorphan and dextrorphan concentrations in plasma and urine were analysed using a previously reported methods by Zimova et al [27] and Jurica et al [28] with modifications. Dextromethorphan hydrobromide syrup (Tussipect R ), (Belgium) 1.5mg/mL was supplied, in part, free by Benjamin Michael Pharmacy, Lagos, Nigeria.…”
Section: Methodsmentioning
confidence: 99%
“…In one study in healthy Caucasian subjects, the DMR from urine collected over the time interval 0-4 h after the dose correlated reasonably well with those determined from plasma concentrations obtained at 3 h [123]. More recently, it has been shown that the DMRs determined using 0-8 h urine collection or a serum sample at 3 h postdose also correlate well with each other [124]. There is also available a 13 C-dextromethorphan breath test.…”
Section: Phenotyping Protocolsmentioning
confidence: 78%
“…Currently, the accepted phenotyping procedure consists of the determination of metabolic ratios (proportion between the amounts of unchanged drug and metabolite mediated by a specific isoenzyme) in body fluids, usually plasma and urine, within a certain time following a single-dose administration of the probe drug. Obviously, these procedures require the availability of appropriate analytical methodologies, usually LC-MS/ MS techniques, able to quantify both compounds probe drug and metabolite [61,64,83,86,87].…”
Section: Genetic Biomarkers and Metabolic Phenotypesmentioning
confidence: 99%